2013
DOI: 10.1165/rcmb.2012-0500oc
|View full text |Cite
|
Sign up to set email alerts
|

An IL-4/IL-13 Dual Antagonist Reduces Lung Inflammation, Airway Hyperresponsiveness, and IgE Production in Mice

Abstract: IL-4 and IL-13 comprise promising targets for therapeutic interventions in asthma and other Th2-associated diseases, but agents targeting either IL-4 or IL-13 alone have shown limited efficacy in human clinical studies. Because these cytokines may involve redundant function, dual targeting holds promise for achieving greater efficacy. We describe a bifunctional therapeutic targeting IL-4 and IL-13, developed by a combination of specific binding domains. IL-4-targeted and IL-13-targeted single chain variable fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 67 publications
1
35
0
Order By: Relevance
“…Future therapeutic approaches in early preclinical development include bispecific antibodies targeting both IL-4 and IL-13 [181,182] which offer an alternative route from targeting IL-4Ra to achieve functional blockade of both IL-4 and IL-13. There is also an inhaled IL-13 antibody fragment [183,184] that could potentially offer the efficacy of systemically dosed mAbs via a more convenient route.…”
Section: Clinical Experiencementioning
confidence: 99%
“…Future therapeutic approaches in early preclinical development include bispecific antibodies targeting both IL-4 and IL-13 [181,182] which offer an alternative route from targeting IL-4Ra to achieve functional blockade of both IL-4 and IL-13. There is also an inhaled IL-13 antibody fragment [183,184] that could potentially offer the efficacy of systemically dosed mAbs via a more convenient route.…”
Section: Clinical Experiencementioning
confidence: 99%
“…One example is a biologic agent targeting both murine IL-4 and IL-13 that was generated by combining well-characterised binding domains in an optimal configuration, using appropriate linker regions [83]. The bifunctional IL-4 and IL-13 antagonist demonstrated high affinity for both cytokines, and reduced the IL-4-dependent rise in serum IgE, and reduced IL-13-dependent airway hyperresponsiveness, lung inflammation, mucin gene expression and serum chitinase responses in mice.…”
Section: Bifunctional Anti-inflammatory Drugsmentioning
confidence: 99%
“…The bifunctional IL-4 and IL-13 antagonist demonstrated high affinity for both cytokines, and reduced the IL-4-dependent rise in serum IgE, and reduced IL-13-dependent airway hyperresponsiveness, lung inflammation, mucin gene expression and serum chitinase responses in mice. Effective dual blockade of IL-13 and IL-4 resulted in greater therapeutic benefit than was achieved by targeting either cytokine alone [83], and clinical trial results of such an approach are awaited with interest.…”
Section: Bifunctional Anti-inflammatory Drugsmentioning
confidence: 99%
“…In particular, IL-4 is considered to be the predominant cytokine of the Th2 pathway in allergic airway inflammation. Briefly, in asthma pathogenesis, IL-4 induces differentiation of Th2 lymphocytes from naive T cells leading to Th2 cytokine release; IL-4 induces the IgE isotype switch and mucus secretion; IL-4 then induces the adhesion molecules on endothelial cells leading to the promotion of fibrosis and thrombosis and primes the vessel wall for eosinophil extravasation [44]. IL-4 has been reported as a trigger for barrier dysfunction in airway epithelial cells, but another study found that only Th1 cytokines affect epithelial barrier function [99].…”
Section: Interleukinsmentioning
confidence: 99%